Thematic Study of the Concept of 'Ilm in the Qur'an and its Relation to the Development of Artificial Intelligence - Ainun Murziq; Andri Nirwana AN; Rozi Irfan Rosyadi (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: this study is to explore the concept of 'ilm in the Qur'an and its relevance to the development of artificial intelligence (AI). Theoretical framework: this is used based on thematic interpretation (maudhū'ī) of the verses of the Qur'an containing the word 'ilm and its derivatives, as well as Islamic philosophical and ethical approaches in the development of science and technology. Literature review: includes literature on the relationship between Islam and technology, interpretation of Qur'anic verses regarding science, and Islamic ethical principles in the development of science. Methods: What is used is library research with a thematic interpretation approach, through the analysis of relevant verses based on the context of asbāb al-nuzūl and the interpretation of classical and contemporary mufasir. Results: research shows that the Qur'an emphasizes the importance of seeking knowledge for the benefit of humans, which is in line with the basic principles of AI development. However, this study also emphasizes the importance of integrating Islamic ethical values in AI applications so that the technology truly benefits humanity. Implications: These findings suggest that Islamic principles, particularly those contained in the Qur'an, can be a moral framework in the development of AI, with an emphasis on responsibility, justice, and social well-being in technological advancement. Novelty: this research lies in an integrative approach between the interpretation of the Qur'an and the contemporary issue of artificial intelligence, which offers a new perspective on the contribution of Islamic ethics in the development of modern technology.